Rest in peace: Reconciling reformed funeral practices with protestant views on intercession - Mudau, Ndidzulafhi (Theologia Viatorum (Sorenga), 2025)
Contemporary reformed funerals often incorporate expressions such as ‘rest in peace’ and ‘provide us a place’, which seem to contradict traditional Protestant doctrine regarding the intercession of saints and the condition of the deceased. Academic inquiry within reformed contexts generates a theological tension. This article analyses the prohibitions imposed by 16th-century Protestant theology on certain behaviours in reformed funerals, emphasising post-mortem agency. This study analyses the influence of reformed interpretations of death and the afterlife on contemporary funeral rituals by a thorough examination of reformation-era documents, reformed confessions and current theological literature employing historical-theological methodology. Contemporary reformed funerals necessitate a theological reassessment, rather than forsaking them for the sake of pastoral sensitivity, which remains significantly relevant. This work enhances reformed practical theology by providing the inaugural comprehensive examination of the theological conflicts between traditional Protestant doctrine and modern funeral practices while also proposing future pathways for theologically robust pastoral care.ContributionThis work enhances reformed practical theology by providing the inaugural comprehensive examination of the theological conflicts between traditional Protestant doctrine and modern funeral practices while also proposing future pathways for theologically robust pastoral care.